1997
DOI: 10.1002/(sici)1096-9861(19970407)380:2<243::aid-cne7>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ontogeny of the epidermal growth factor receptor and its ligand, transforming growth factor alpha, in the rat brain

Abstract: Transforming growth factor alpha (TGF alpha) interacts with the epidermal growth factor receptor (EGF-R) to produce its biological effects. TGF alpha induces the proliferation and differentiation of central nervous system (CNS) astrocytes and pluripotent stem cells, as well as the survival and differentiation of postmitotic CNS neurons. Both TGF alpha and EGF-R have been localized to the postnatal CNS. As the majority of CNS neuronal proliferation and migration occurs antenatally, we have examined the ontogeny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(106 citation statements)
references
References 57 publications
7
99
0
Order By: Relevance
“…[1][2][3]44 EGF production declines during brain development, while expression of HB-EGF and TGFa is increased. 45,46 In fact, EGFR are expressed on pyramidal neurons, interneurons, and glial cells in the postnatal neocortex and striatum, suggesting that they have biological actions in these cells. 47,48 Herein, we demonstrated that peripherally administered EGF can act over and above endogenous EGF in the brain as monitored by phosphorylation of EGFR.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3]44 EGF production declines during brain development, while expression of HB-EGF and TGFa is increased. 45,46 In fact, EGFR are expressed on pyramidal neurons, interneurons, and glial cells in the postnatal neocortex and striatum, suggesting that they have biological actions in these cells. 47,48 Herein, we demonstrated that peripherally administered EGF can act over and above endogenous EGF in the brain as monitored by phosphorylation of EGFR.…”
Section: Figurementioning
confidence: 99%
“…Neural stem cells from the adult subventricular zone can be expanded and maintained in vitro under the influence of fibroblast growth factor 2 (FGF2) and epidermal growth factor (EGF); these observations suggested that FGF2 and EGF might also act in vivo [84][85][86][87][88]. Indeed, knockout mice for FGF2 or transforming growth factor-α, a ligand for EGF receptor, exhibit decreased neurogenesis in the SVZ, and fewer neurons recruited to the olfactory bulb [89,90].…”
Section: Mitogens Can Trigger Adult Neurogenesis In Vivomentioning
confidence: 99%
“…Another tyrosine kinase receptor, EGFR, is also implicated in the regulation of radial migration in the developing cerebral cortex. EGFR and its ligands, including heparin-binding EGF (HB-EGF) and TGF␣, are expressed in the developing cortex (Kornblum et al, 1997;Nakagawa et al, 1998). EGFR-targeted disruption and EGFR overexpression studies showed that EGFR is involved in normal radial migration (Threadgill et al, 1995;Caric et al, 2001).…”
Section: A Potential Role Of P-rex1 In Neuronal Migrationmentioning
confidence: 99%